Genera of aquatic insects from Costa Rica, deposited at the Museo de Zoología, Universidad de Costa Rica - Springer, Monika (1998)
A first checklist of the genera of aquatic insects from Costa Rica is presented. The material has been collected since 1990 throughout the entire country and is deposited at the Museo de Zoología, Universidad de Costa Rica. The collection includes only the aquatic stages from each order and contains a total of 278 genera from 92 families in 11 orders.